If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -21 = 9b + 6 Reorder the terms: -21 = 6 + 9b Solving -21 = 6 + 9b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9b' to each side of the equation. -21 + -9b = 6 + 9b + -9b Combine like terms: 9b + -9b = 0 -21 + -9b = 6 + 0 -21 + -9b = 6 Add '21' to each side of the equation. -21 + 21 + -9b = 6 + 21 Combine like terms: -21 + 21 = 0 0 + -9b = 6 + 21 -9b = 6 + 21 Combine like terms: 6 + 21 = 27 -9b = 27 Divide each side by '-9'. b = -3 Simplifying b = -3
| 4q+3=9q-17 | | 53=x | | 7x-12=3x+46 | | 3-x=5x-15 | | 3t+1=-8 | | 2x+15=-47-10x | | 9x^4-18x^3-x^2+2x= | | 9x^4-18x^3-x^2+2x=0 | | (24q^2-16q)= | | (2x+6)=10 | | 15-25/4*2= | | 3(1-x)+2=7 | | x+a/a=b+c/c | | 14x-21=7 | | x^2-10x+6=-7 | | 118-2x=25x+19 | | -8x-7y=-56 | | 6x+-1=15x-82 | | 13=6e^3x | | x^2+(2*x)/(x-1)=8 | | y(2y)= | | 5x+16=7x-8 | | y(3-2y)= | | 7/3y=56/3 | | 14/62 | | 9-3+4= | | 2(7x+4)=148 | | 3x=-y+10 | | 186-6x=5+21 | | (-2y+20/3)+3y=-12 | | -8(3x-1)=-7(2x+4) | | 4/7x-6/5=5x+3/2 |